PENGARUH EKSTRAK KULIT BUAH MANGGIS (Garcinia mangostana L.) TERHADAP SIKLUS ESTRUS MENCIT (Mus musculus L. Swiss Webster) - Maria Gorette, Julia; Sumarmin, Ramadhan; Widiana, Rina (Pendidikan Biologi, 2014)
ABSTRACTMangosteen (Garcinia mangostana L.) is a tropical plant that originated from Southeast Asia. Mangosteenrindis used to treat various diseases, antihistamine, antibacterial, anti-cancer, anti-hypertension and stroke. This study aims to determine the effect of extracts of mangosteen rind (Garcinia mangostana L.) on the estrous cycle of mice (Mus musculus L. Swiss Webster). This study is an experiment used Completely Randomized Design ( CRD ), 4 treatments and 6 replications. Mangosteen peel extract given to mice by gavage for 24 days way. The extract was given to mice at a dose of B 0.2, C 0.4, D 0.6 and Control A 0 g /head/day. Observations made during the estrous cycle of 26 days to review the vaginal smear method with stained Giemsa. The data obtained were analyzed by Analysis of Variance by analyzing the average length of one cycle and each phase of the estrous cycle of mice and Duncan New Multiple Range Test (DNMRT).The results showed mangosteen peel extract can prolong the estrous cycle during the (± 3 days) and extension occurred in all phases of the cycle (proestrus, estrous, and diestrus, metestrus ). Added time proestrus phase of the shortest found in A (1.25 days) and longest in treatment C (2 days). Estrous phase of the shortest found in A (2.13 days) and longest in treatment D (3 days). Metestrus phase the shortest found in A (1.71 days) and longest in treatment D (3.58 days). Diestrus phase of the shortest found in A ( 1.42 days ) and longest in treatment D ( 3.52 days ). Added estrous cycle at a time (6.5 days), B (9.33 days), C (10.07 days) and D (11.53 days). From these results it can be concluded that mangosteen peel extract given orally prolong the estrous cycle and extension at each phase of the estrous cycle